Patterns of change in cytochrome c oxidase redox status - Gagnon, Roy E.; Macnab, Andrew J.; LeBlanc, Jacques G. (Journal of spectroscopy (Hindawi), 2004)
Investigators using mono channel near infrared spectroscopy (NIRS) have reported different patterns of change in cytochrome c oxidase (Cyt) in similar studies of tissue ischaemia. We investigated whether there were distinctive differences in NIRS signals obtained simultaneously from different sampling sites during the same imposed physiological intervention within the same subject. Methods : Subjects were 36, healthy, 10 kg, commercial swine undergoing cardiopulmonary bypass to initiate 3 to 7 periods of 7.5 minutes of circulatory arrest. Each arrest was initiated at one of 81 combinations of high, normal, or low levels of core temperature, haematocrit, pH, and serum glucose. Each combination was repeated twice, yielding 162 NIRS data sets. Results : Six distinct patterns of change of Cyt were found. Typically, brain Cyt quickly became reduced shortly after the start of arrest, muscle Cyt did not start becoming reduced until after 3½ minutes of arrest, and spinal cord Cyt either did not change status or became gradually reduced throughout the period of arrest. The brain response may reflect strong oxygen dependence, while the muscle response may indicate a dependency buffered by myoglobin stores, and the spine response may indicate a low concentration of available Cyt that is too diffuse to be rapidly influenced by changes in oxygen availability. Conclusion : Multi‒channel NIRS is needed for systemic evaluation of respiration at the cellular level in clinical settings. Distinctive Cyt patterns of change occur in different organs at the same time, in response to circulatory arrest.